2014
DOI: 10.5713/ajas.2013.13385
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide Association Study of Integrated Meat Quality-related Traits of the Duroc Pig Breed

Abstract: The increasing importance of meat quality has implications for animal breeding programs. Research has revealed much about the genetic background of pigs, and many studies have revealed the importance of various genetic factors. Since meat quality is a complex trait which is affected by many factors, consideration of the overall phenotype is very useful to study meat quality. For integrating the phenotypes, we used principle component analysis (PCA). The significant SNPs refer to results of the GRAMMAR method a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 27 publications
0
20
0
Order By: Relevance
“…This gene has been shown to impact meat quality (Lee et al, 2014). As a member of the hedgehog-signaling pathway, BMP6 may be important in slow oxidative fiber clustering in pigs (Lee et al, 2014). Hence, selection for desirable alleles of BMP6 may increase iron homeostasis and increase oxidative fiber clustering, which could in turn increase myoglobin concentration in the meat.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This gene has been shown to impact meat quality (Lee et al, 2014). As a member of the hedgehog-signaling pathway, BMP6 may be important in slow oxidative fiber clustering in pigs (Lee et al, 2014). Hence, selection for desirable alleles of BMP6 may increase iron homeostasis and increase oxidative fiber clustering, which could in turn increase myoglobin concentration in the meat.…”
Section: Discussionmentioning
confidence: 99%
“…Bone morphogenetic protein 6 (BMP6), located in the region SSC 7_4 Mb, regulates a range of biological processes, including iron homeostasis, ovulation, and bone and fat development. This gene has been shown to impact meat quality (Lee et al, 2014). As a member of the hedgehog-signaling pathway, BMP6 may be important in slow oxidative fiber clustering in pigs (Lee et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…At present, studies of BMP6 showed that it is more focused on human disease such as hepatic fibrosis, iron overload disease (Kleven et al, 2016), prostate cancer-associated disease (Turner and Edwards, 2016) and so on. Nevertheless, BMP6 was chose to be a candidate of meat quality (Lee et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Over the past 20 years, the dense genome coverage provided by high-throughput chip genotyping makes it possible to exploit the linkage disequilibrium (LD) between single nucleotide polymorphisms (SNPs) and quantitative trait locus (QTL) through genome-wide association study (GWAS) to identify genes related to traits of interest. Several GWAS have been revealed significant associations for economically important traits such as reproduction traits [5], growth traits [6], meat traits [7], and feed conversion [8].…”
Section: Introductionmentioning
confidence: 99%